Risk factors and musculoskeletal disorder complaints among desk workers at PDAM Tirtanadi, Medan City - Vanessa Gafar; Cristyn Renata Situmorang; Santy Deasy Siregar; Roslenni Sitepu; Imelda Montes Monika Simanungkalit (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2026)
Background: Musculoskeletal disorders (MSDs) represent a major occupational health concern, especially among computer-based workers. This study examined individual and occupational risk factors associated with MSD complaint levels among workers at PDAM Tirtanadi in Medan City. Method: Using an analytical cross-sectional survey design, we recruited 150 respondents through purposive sampling. Data collection involved the Nordic Musculoskeletal Questionnaire to assess MSD complaints and the Rapid Office Strain Assessment (ROSA) to evaluate work postures. Analysis employed the chi-square test. Results: Most workers (64.0%) reported high MSD complaint levels. Bivariate analysis showed significant associations with work posture, age, and work tenure. High-risk work posture emerged as the dominant factor: 83.8% of workers in this category reported high MSD complaint levels. Older age (69.3%) and longer work tenure (69.4%) also associated with high MSD complaint levels. No significant associations appeared with gender (p=0.146) or body mass index (p=0.718). Conclusion: Non-ergonomic work postures, older age, and longer work tenure were the primary predictors of MSD complaints in this population. Management should implement an ergonomics program that addresses workstation design, posture training, and work scheduling to promote worker health.